4x-2+6(x-4)=3+2x

Simple and best practice solution for 4x-2+6(x-4)=3+2x equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 4x-2+6(x-4)=3+2x equation:


Simplifying
4x + -2 + 6(x + -4) = 3 + 2x

Reorder the terms:
4x + -2 + 6(-4 + x) = 3 + 2x
4x + -2 + (-4 * 6 + x * 6) = 3 + 2x
4x + -2 + (-24 + 6x) = 3 + 2x

Reorder the terms:
-2 + -24 + 4x + 6x = 3 + 2x

Combine like terms: -2 + -24 = -26
-26 + 4x + 6x = 3 + 2x

Combine like terms: 4x + 6x = 10x
-26 + 10x = 3 + 2x

Solving
-26 + 10x = 3 + 2x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-2x' to each side of the equation.
-26 + 10x + -2x = 3 + 2x + -2x

Combine like terms: 10x + -2x = 8x
-26 + 8x = 3 + 2x + -2x

Combine like terms: 2x + -2x = 0
-26 + 8x = 3 + 0
-26 + 8x = 3

Add '26' to each side of the equation.
-26 + 26 + 8x = 3 + 26

Combine like terms: -26 + 26 = 0
0 + 8x = 3 + 26
8x = 3 + 26

Combine like terms: 3 + 26 = 29
8x = 29

Divide each side by '8'.
x = 3.625

Simplifying
x = 3.625

See similar equations:

| 9(7x-2)= | | 3x(x+10)+4(x+20)+5x=185-3x | | 5n-14=41 | | 4*n=1 | | 2(2y-1)+y=3 | | 2(x+4)=2(-8-x)-2x | | (2x+3)x=50 | | 13-6d/7=7 | | 2+3q=4q | | B+1=-5b+5 | | -8(32x+13)=26(16-6x) | | 2+2x-5=5(x+3) | | 6(18+5x)= | | 10=3.1 | | 5(c+12)=2c+18 | | -18x+4-12x-10=9-6x-3 | | 3w-9+2(3w+5)=-5(w+1) | | -7(1+8v)=-399 | | (10x-8)+(2x+9)= | | 4(x+3)=3x+2+x | | -2-(5-6p)= | | 9x+(y)i-5=12i+4 | | -3(-8+4n)=2(2-8n) | | -5x=-50+5(4x-10) | | 3n-144=2n-32 | | 2/3x-1=4 | | .375x-.75=.125x | | 3z-(z-4)=10 | | 100[0.05(m+5)]= | | 3x-2(5x-10)=-1 | | 2n-144=2n-32 | | 7x-.5=5a+2.3 |

Equations solver categories